(3eSfO GdHRGQs - (3CHh HcQ CMeO Hf YeQh Hf YHO GdNGdb GdHRGQ,J (B292 (3g` s
(3ChdgG (B:s
(3jHJOF HMOjK GdfVQ Hf CfS s
(3BNQgG (B:s
(3hjfJgi HMOjK CHj eYjf Yf CHj UGdM s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B100 s
Keywords: (3GdMOjK h GdeUWdMs